USAHA BUNUH DIRI BERDASARKAN TEORI EKOLOGI BRONFENBRENNER - Witrin Gamayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2014)
The research examine about attempted suicide an ecological Bronfenbrenner approach. The purpose of this research is to enhance our understanding about description dynamic attempted suicide. The ecological Bronfenbrenner approach allows exploration of how person whom attempted suicide is determined by multiple factors these are microsystem, mesosystem, exosystem, macrosystem, chronosystemdanontogenic system. This research is case study, qualitative method on two young women. Woman who attempted suicide is someone who intentionally injures herself but does not die. The measurement tool used deep interview and observation. The results showed that theecological influenced to decide attempted suicide.